Model predictive disturbance rejection during cooperative mobile robot assembly tasks - Sujan,V. A. (2004)
This paper addresses the problem of disturbance compensation for the successful assembly of structures by mobile field robots. A control architecture, consisting of a linear PID joint controller with model predictive feed-forward compensation for mobile base motions and interactive-force disturbance rejection is discussed. Object insertion is achieved by predicting environment-object contact states and motions are planned in the direction of least resistance. Issues addressed include dynamic modeling of multiple cooperative robots, control architecture design and stability analysis, and environment-object contact state prediction. Simulation results show the effectiveness of the control architecture.